Reframing Digital Innovation in EFL Classrooms: A Pedagogical Autoethnography of Teacher-Developed Offline Gamified Powerpoint Media - Ikrar, Ikrar (Jurnal Locus Penelitian dan Pengabdian, 2026)
Digital innovation in English language learning is often associated with high-tech platforms such as internet-based systems and mobile applications, which overlooks disparities in access and digital literacy across many regions. This study explores alternative forms of digital innovation that are more inclusive and sustainable. It aims to investigate the use of offline gamified PowerPoint media developed by teachers as a low-tech instructional alternative, with a focus on sustainability and equity in EFL classrooms. Adopting a pedagogical autoethnography approach, data were collected through reflective journals, classroom observations, student feedback, and instructional artifacts over two academic years. Triangulation and thematic analysis were employed to ensure methodological rigor. The findings reveal three key transformations: (1) reconstruction of teacher identity as a learning designer, (2) increased student engagement and reduced speaking anxiety through gamified interaction, and (3) the emergence of offline gamified pedagogy as a sustainable and equity-oriented model of digital innovation. This study demonstrates that low-tech, pedagogically grounded digital innovation can serve as an effective and sustainable alternative, even in resource-constrained contexts, while supporting inclusive and high-quality learning experiences.